2020
DOI: 10.1016/j.onehlt.2020.100185
|View full text |Cite|
|
Sign up to set email alerts
|

“One health" inspired SARS-CoV-2 surveillance: The Galapagos Islands experience

Abstract: The COVID-19 pandemic has spread worldwide since the outbreak in Wuhan (China) in December 2019, currently infecting over 25 million people and causing more than 800.000 deaths. In Ecuador, up to the 30th of August 2020, overall 113.648 confirmed cases and 6.555 deaths have been declared. Besides overloading of hospital, capacity for molecular diagnosis of SARS-CoV-2 by the Ministry of Public Health was quickly overwhelmed. In this context, emergency authorization for SARS-CoV-2 RT-qPCR diagnosis was granted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…The viral loads detailed on Table 2 were calculated running a calibration curve with 2019-nCoV N positive control (IDT, USA). The LoD for the CDC protocol was set at 1000 viral RNA copy per mL of sample (or 5 RNA copies/µL of RNA extraction solution) on previous studies [2,6,[8][9][10][11]. Although LoD could not be calculated for "AccuPower SARS-CoV-2 Real Time RT-PCR kit" as we described on the methods, no true positive samples were obtained below 40.000 RNA copies/mL of sample (200 RNA copies/µL of RNA extraction solution) according to the CDC protocol; even the sample 13617 (Table 2) with a viral load of 453 copies/µL (90,600 copies/mL of sample) was not detected by "AccuPower SARS-CoV-2 Real Time RT-PCR kit".…”
Section: Estimation Of the Limit Of Detection Of "Accupower Sars-cov-mentioning
confidence: 99%
“…The viral loads detailed on Table 2 were calculated running a calibration curve with 2019-nCoV N positive control (IDT, USA). The LoD for the CDC protocol was set at 1000 viral RNA copy per mL of sample (or 5 RNA copies/µL of RNA extraction solution) on previous studies [2,6,[8][9][10][11]. Although LoD could not be calculated for "AccuPower SARS-CoV-2 Real Time RT-PCR kit" as we described on the methods, no true positive samples were obtained below 40.000 RNA copies/mL of sample (200 RNA copies/µL of RNA extraction solution) according to the CDC protocol; even the sample 13617 (Table 2) with a viral load of 453 copies/µL (90,600 copies/mL of sample) was not detected by "AccuPower SARS-CoV-2 Real Time RT-PCR kit".…”
Section: Estimation Of the Limit Of Detection Of "Accupower Sars-cov-mentioning
confidence: 99%
“…As the LoD of 2019-nCoV Nucleic Acid Diagnostic Kit (Sansure Biotech) is 1 copie/μL according to the manufacturers, these three "false-positive" samples would be actually true-positive SARS-CoV-2 samples that are below the LoD of the CDC protocol. [7][8][9][10][11] So the real specificity for 2019-nCoV Nucleic Acid Diagnostic Kit (Sansure Biotech) is 100%.…”
Section: Resultsmentioning
confidence: 99%
“…All the samples included on the study were tested following an adapted version of the CDC protocol: (1) using AccuPrep Viral RNA extraction kit (Bioneer, Daejeon, South Korea) as an alternate RNA extraction method, and (2) using CFX96 BioRad instrument. [8][9][10][11][12] RT-qPCR for SARS-CoV-2 diagnosis using COVID-19 Nucleic Acid Test Kit (eDiagnosis). Same RNA extractions from all the samples included in the study were tested using COVID-19 Nucleic Acid Test Kit (eDiagnosis), following the manufacturer's manual.…”
Section: Methodsmentioning
confidence: 99%
“…All of the samples included in the study were tested following an adapted version of the CDC protocol reported previously by our laboratory ( Freire-Paspuel et al, 2020b , Freire-Paspuel et al, 2020c , Freire-Paspuel and Garcia-Bereguiain, 2020a , Freire-Paspuel et al, 2020 , Freire-Paspuel and Garcia-Bereguiain, 2020b , Freire-Paspuel et al, 2020d ).…”
Section: Methodsmentioning
confidence: 99%